A near-fatal case of sepsis with an antibiotic-resistant organism complicating a routine transrectal prostate biopsy in a health care worker - Weber, Bryce; Saliken, John; Jadavji, Taj; Gray, Robin R.; Moore, Ronald (Canadian Urological Association Journal, 2013)
A 58-year-old physician with an elevated prostate specific antigen developed severe septic shock following a repeat transrectal prostate biopsy despite standard preoperative prophylactic protocol. This case highlights the significance of harbouring antibiotic-resistant bacteria and the risk of previous quinolone exposure. We believe this case may herald a rare but potentially serious consequence of increasingly common antibiotic resistance and that high-risk patients should be studied to determine their likelihood of carrying antibiotic-resistant flora in their genitourinary/gastrointestinal tract.